Gata4 is required for maintenance of postnatal cardiac function and protection from pressure overload-induced heart failure - Bisping, Egbert (National Academy of Sciences, 2006)
An important event in the pathogenesis of heart failure is the development of pathological cardiac hypertrophy. In cultured cardiomyocytes, the transcription factor Gata4 is required for agonist-induced hypertrophy. We hypothesized that, in the intact organism, Gata4 is an important regulator of postnatal heart function and of the hypertrophic response of the heart to pathological stress. To test this hypothesis, we studied mice heterozygous for deletion of the second exon of Gata4 (G4D). At baseline, G4D mice had mild systolic and diastolic dysfunction associated with reduced heart weight and decreased cardiomyocyte number. After transverse aortic constriction (TAC), G4D mice developed overt heart failure and eccentric cardiac hypertrophy, associated with significantly increased fibrosis and cardiomyocyte apoptosis. Inhibition of apoptosis by overexpression of the insulin-like growth factor 1 receptor prevented TAC-induced heart failure in G4D mice. Unlike WT-TAC controls, G4D-TAC cardiomyocytes hypertrophied by increasing in length more than width. Gene expression profiling revealed up-regulation of genes associated with apoptosis and fibrosis, including members of the TGF-β pathway. Our data demonstrate that Gata4 is essential for cardiac function in the postnatal heart. After pressure overload, Gata4 regulates the pattern of cardiomyocyte hypertrophy and protects the heart from load-induced failure.